The Cheese Matrix Modulates the Immunomodulatory Properties of Propionibacterium freudenreichii CIRM-BIA 129 in Healthy Piglets - Rabah, Houem; Ferret-Bernard, Stéphanie; Huang, Song; Le Normand, Laurence; Cousin, Fabien J.; Gaucher, Floriane; Jeantet, Romain; Boudry, Gaëlle; Jan, Gwénaël (Frontiers in Microbiology, 2018)
Propionibacterium freudenreichii is a beneficial bacterium, used as a cheese starter, which presents versatile probiotic properties. These properties are strain-dependent. We hypothesized they may also be delivery vehicle-dependent. In this study, we thus explored in healthy piglets how the cheese matrix affects the immunomodulatory properties of P. freudenreichii. During 2 weeks, three groups of weaned piglets consumed, respectively, P. freudenreichii as a liquid culture (PF-culture), P. freudenreichii under the form of a cheese (PF-cheese), or a control sterile cheese matrix (Cheese-matrix). The in vivo metabolic activity of P. freudenreichii was assessed by determining short chain fatty acids (SCFA) concentration and bifidobacteria population in feces. Whatever the delivery vehicle, P. freudenreichii was metabolically active in piglets’ colon and enhanced both bifidobacteria and SCFA in feces. P. freudenreichii consumption decreased the secretion of TNFα and of IL-10 by peripheral blood mononuclear cells (PBMC). It did not alter IL-10, IFNγ, IL-17, and TNFα secretion in mesenteric lymph node immune cells (MLNC). PF-cheese enhanced significantly Treg phenotype, while PF-culture decreased significantly Th17 phenotype in PBMC and MLNC. Remarkably, only PF-cheese induced an increase of Th2 phenotype in PBMC and MLNC. Ex vivo stimulation of PBMC and MLNC by Lipopolysaccharides and Concanavalin A emphasized the difference in the immunomodulatory responses between PF-culture and PF-cheese group, as well as between PBMC and MLNC. This study shows the importance to consider the delivery vehicle for probiotic administration. It confirms the anti-inflammatory potential of P. freudenreichii. It opens new perspectives for the use propionibacteria-fermented products as preventive agents for inflammatory bowel diseases and intestinal infectious diseases.